Podjetniška demografija in značilnosti podjetništva mladih: Slovenski podjetniški observatorij 2023 - Širec, Karin; Bradač Hojnik, Barbara; Močnik, Dijana (University of Maribor Press, 2024)
Entrepreneurial Demographics and Characteristics of Youth Entrepreneurship: Slovenian Entrepreneurship Observatory 2023. The Slovenian Entrepreneurship Observatory 2023 examined the demographics of Slovenian companies and the characteristics of youth entrepreneurship in Slovenia and in comparison with Europe. In the first part of the Slovenian Entrepreneurship Observatory study, we analysed the demographic characteristics of Slovenian companies, while the second part was devoted to a topical issue in both the Slovenian and the European economy, the analysis of youth entrepreneurship. The demographic analysis was aimed at understanding the profiles of Slovenian companies based on various criteria such as the number of companies, their size, revenue generated, labour costs and value added, broken down by industry, region and company size. The study of the characteristics of youth entrepreneurship provided insights into the dynamics of entrepreneurship in the selected target group in order to design effective measures to promote the development of youth entrepreneurship.